2012
DOI: 10.3109/09553002.2012.702296
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular effects of Auger emitters: 2008–2011

Abstract: Significant progress can be reported for targeting methods and improvements in methods to accumulate Auger emitters in the target cells, as well as advances in dose calculations. These studies further our understanding of how Auger emitters induce cell death at a cellular and molecular level, supporting the targeted radiomedical applications of Auger emitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This strongly suggested that it was radiosensitization by Pt that caused the decrease in cell survival rather than the intrinsic cytotoxicity of the sensitizer used in combination with LEX. Although most of the enhancement in radiosensitization from the 160-kV source occurs from X-rays below the K-edge, it follows that the corresponding cell survival due to Pt Auger decays in proximity to cell nuclei versus cytoplasm [ 37 ] was higher with 6-MV photons.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggested that it was radiosensitization by Pt that caused the decrease in cell survival rather than the intrinsic cytotoxicity of the sensitizer used in combination with LEX. Although most of the enhancement in radiosensitization from the 160-kV source occurs from X-rays below the K-edge, it follows that the corresponding cell survival due to Pt Auger decays in proximity to cell nuclei versus cytoplasm [ 37 ] was higher with 6-MV photons.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the dose-limiting organ in targeted radionuclide therapy (TRT) is the bone marrow (Sgouros, 2007;Sgouros et al, 2000). Auger-electron emitters are attractive candidate radionuclides in TRT of disseminated diseases (and micrometastasis) due to a vanishing cross-irradiation effect which spares healthy cells in the vicinity of the targeted cells (Fischer et al, 2008;Kassis, 2011Kassis, , 2004Yasui, 2012). It has been reported (Behr et al, 2000;Boswell and Brechbiel, 2005) that Auger emitters (I-125, In-111) may exhibit better therapeutic effect, when bound to an internalizing monoclonal antibody, than β À -emitters (I-131, Y-90) which have been used successfully in the treatment of non-Hodgkins' lymphoma Pouget et al, 2011;Song and Sgouros, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Auger electrons have a very low energy (from a few eV to few keV) and those with energy below 1 keV are considered as high LET particles (from 4 to 26 keV/µm). Their path length in biological matter is very short, between about 2 nm and 500 nm ( [20] and for reviews see [3,4,6,11,12,19,32]), and they produce highly localized energy deposits. They have been mostly used for targeting the nucleus [1,13,14].…”
Section: Introductionmentioning
confidence: 99%